21st century quality: Looking into the “Crystal ball” - Fonseca, Luís Miguel Ciravegna (2016)
The discussion of possible scenarios for the future of Quality is on the priority list of major Quality Practitioners Societies. EOQ – European Organization for Quality (EOQ, 2014) main team for its 58th EOQ-Congress held June 2014 in Göteborg was “Managing Challenges in Quality Leadership” and ASQ - American Society for Quality (ASQ, 2015) appointed “the Future of Quality” for Quality Progress Magazine November 2015 issue. In addition, the ISO 9001:2008 revision process carried by ISO/TC 176 aims to assure that ISO 9001:2015 International Standard remains stable for the next 10 years (ISO, 2014) contributing to an increased discussion on the future of quality. The purpose of this research is to review available Quality Management approaches and outline, adding an academic perspective, expected developments for Quality within the 21st Century. This paper follows a qualitative approach, although data from international organizations is used. A literature review has been undertaken on quality management past and potential future trends. Based on these findings a model is proposed for organization quality management development and propositions for the future of quality management are advanced. Firstly, a state of the art of existing Quality Management approaches is presented, for example, like Total Quality Management (TQM) and Quality Gurus, ISO 9000 International Standards Series (with an outline of the expected changes for ISO 9001:2015), Six Sigma and Business Excellence Models.Secondly, building on theoretical and managerial approaches, a two dimensional matrix – Quality Engineering (QE - technical aspects of quality) and Quality Management (QM: soft aspects of quality) - is presented, outlining five proposed characterizations of Quality maturity levels and giving insights for applications and future developments. Literature review highlights that QM and QE may be addressing similar quality issues but their approaches are different in terms of scope breadth and intensity and they ought to complement and reciprocally reinforce one another. The challenges organizations face within the 21st century have stronger uncertainty, complexity, and differentiation. Two main propositions are advanced as relevant for 21st Century Quality: - QM importance for the sustainable success of organizations will increase and they should be aware of the larger ecosystem to be managed for improvement, possibly leading to the emergence of a new Quality paradigm, The Civilizacional Excellence paradigm. - QE should get more attention from QM and the Quality professionals will have to: a) Master and apply in wider contexts and in additional depth the Quality Tools (basic, intermediate and advanced); b) Have the soft skills needed for its success; c) Be results oriented and better understand and demonstrate the relationships between approaches and results These propositions challenge both scholars and practitioners for a sustained and supported discussion on the future of Quality. “All things are ready, if our mind be so.” (Shakespeare, Henry V, circa 1599).